PENGUKURAN KINERJA PERUSAHAAN BERDASARKAN BALANCE SCORECARD PADA PT. BPR NBP 17 SUNGGAL MEDAN - Situmeang, Nico M.T. (UNIKA Santo Thomas, 2012)
The purpose of this study was to measure the performance of companies BPR NBP 17 based on the Balanced Scorecard. The population in this study are the financial statements and reports that are non-financial since starting up in 1995 to 2011. The sample was non-financial data and financial data is for 3 years ie 2009-2011. Data collection techniques in this study is a documentation technique. Techniques of data analysis in this research is descriptive method. From the results of research and discussion, it is concluded that the level of ROA and ROE 17 BPR NBP increased since 2009-2011, and the increase in customers from year to year, but more emphasis needs to be improved in a more friendly customer service. 17 BPR NBP performance of internal business process perspective is relatively poor. It is shown from the years 2009-2011 the number of customer complaints against the company level has increased from year to year and is still a lack of customer service processes. 17 BPR NBP performance from the perspective of learning and growth is not good. It can be seen from the number of employees who attended training from year to year decline and not programmed training provided toemplo yees of the company.